COVID-19: a brief review (Journal of Pathology of Nepal, 2020)
In December 2019, Wuhan, in China, became the center of an outbreak of pneumonia of unknown cause. In January 2020, a novel coronavirus was identified. Later the whole genomic sequence of this novel virus was established. The World Health Organization named the disease “COVID-19” and marked it as a pandemic. The origin of the virus is still conjectural. Studies suggested markedly increased levels of several pro-inflammatory cytokines and chemokines in these patients, which lead to injury to several organs. The organ which is most commonly damaged is the lungs. On histopathology, lung shows diffuse alveolar damage with hyaline membrane formation. The incubation period ranges from 1-14 days. The clinical features vary widely, from asymptomatic to multi-organ failure and shock. The common clinical features are related to the respiratory system. For diagnosis, oropharyngeal/nasopharyngeal swabs should be collected by Dacron swabs under proper precaution and the samples should be collected in viral transport media. The viral ribonuclei acid is detected by Real Time-Polymerase Chain Reaction. Till now no definite therapy or vaccination is available and the main approach to manage the pandemic is by preventive measures like social distancing, hygiene maintenance, and contact tracing.